Paradigma Pancasila dalam Pengembangan Sastra Indonesia: Perspektif Kajian Hermeneutik di Era Globalisasi - Panjaitan, Ridho Sastro; Barus, Irfansyah; Afarrel, Muhammad Ridho; Manurung, Afriani Sasmita; Pakpahan, Wijar; Yunita, Sri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Globalization encourages strong cultural exchange, which can influence local identities and values ​​in Indonesian literature. The purpose of this study is to examine Pancasila as a normative foundation for the development of Indonesian literature amidst the strong currents of globalization. This research uses a qualitative method with a literature study approach combined with hermeneutic analysis. Data were obtained from secondary sources such as academic journals and documents related to Pancasila, globalization, and literature in Indonesia. The analysis was conducted through in-depth textual interpretation to discover the meaning of Pancasila values ​​in a literary context, a comprehensive understanding, and a synthesis of interpretations. The results show that the five principles of Pancasila serve as the ethical and aesthetic foundation of Indonesian literature, maintaining a balance between global influences and the preservation of local identity. This perspective allows literary works to remain social without losing their cultural roots. This research provides a conceptual contribution to strengthening a literary paradigm based on Pancasila values ​​in literary education, research, and practice, as an effort to strengthen national identity amidst globalization.